Women and homelessness in Ireland : a biographical, longitudinal perspective - Sheridan, Sarah (Trinity College (Dublin, Ireland). School of Social Work and Social Policy, 2017)
This doctoral thesis explores women’s experiences of homelessness and housing stability using a longitudinal qualitative approach. Based in the Republic of Ireland, the study was initiated in the context of a recognised dearth of empirical research on the topic of homelessness among women. Internationally, as well as in Ireland, the knowledge base on women’s homelessness is relatively weak, owing in large part to an historical tendency among research communities to concentrate on the experiences of men, who typically represent a larger proportion of the ‘visible’ homeless population. Many studies have ignored or side-lined the experiences of women, while others have adopted a largely gender-neutral approach. While in more recent years the research base on women’s homelessness has gradually expanded in some Northern European countries, as well as in North America and Australia, women’s homelessness is almost always researched cross-sectionally, yielding a rather static picture of women’s experiences of homelessness and housing instability, as well as a weak understanding of the processes and negotiations associated with their ‘journeys’ or routes through and possibly out of homelessness. This doctoral study aims to redress several gaps in the literature by researching women’s homelessness longitudinally. A core aim is to examine women’s homelessness over time, meaning that their lives and experiences would be viewed through the lens of change through a close examination of their homeless and housing transitions. This study also seeks to explore women’s relationships and interactions with services, their identities and identity transitions, and the meanings women attach to homelessness and home. The study, which is qualitative and longitudinal, integrates biographical interviews with ethnographic observation. At baseline (Phase I of the research), sixty women were recruited to the study between January 2010 and July 2011. All were recruited from homelessness or domestic violence services in the cities of Dublin, Cork and Galway. During this period, ethnographic observation was carried out at four service sites in Dublin city (which has recorded highest numbers of homeless persons in the country). Between November 2012 and September 2013 - approximately three years later - forty of these women were successfully tracked and re-interviewed Phase II of the research. Reliable information on the living situations of an additional nine women was attained at the time of follow-up, though it was not possible to re-interview these women. At Phase II of the study, ethnographic observation was again carried out in four service settings in Dublin city. The study’s retention rate is satisfactory given the recognised challenges associated with retaining transient populations in research of this kind. Methodologically, the study was guided by an interpretivist epistemology, which emphasises individuals’ personal understandings of their social worlds. The research therefore sought to give ‘voice’ to homeless women’s experiences and their perspectives on their lives and situations over time. Grounded in the rich qualitative data garnered This doctoral thesis explores women’s experiences of homelessness and housing stability using a longitudinal qualitative approach. Based in the Republic of Ireland, the study was initiated in the context of a recognised dearth of empirical research on the topic of homelessness among women. Internationally, as well as in Ireland, the knowledge base on women’s homelessness is relatively weak, owing in large part to an historical tendency among research communities to concentrate on the experiences of men, who typically represent a larger proportion of the ‘visible’ homeless population. Many studies have ignored or side-lined the experiences of women, while others have adopted a largely gender-neutral approach. While in more recent years the research base on women’s homelessness has gradually expanded in some Northern European countries, as well as in North America and Australia, women’s homelessness is almost always researched cross-sectionally, yielding a rather static picture of women’s experiences of homelessness and housing instability, as well as a weak understanding of the processes and negotiations associated with their ‘journeys’ or routes through and possibly out of homelessness. This doctoral study aims to redress several gaps in the literature by researching women’s homelessness longitudinally. A core aim is to examine women’s homelessness over time, meaning that their lives and experiences would be viewed through the lens of change through a close examination of their homeless and housing transitions. This study also seeks to explore women’s relationships and interactions with services, their identities and identity transitions, and the meanings women attach to homelessness and home. The study, which is qualitative and longitudinal, integrates biographical interviews with ethnographic observation. At baseline (Phase I of the research), sixty women were recruited to the study between January 2010 and July 2011. All were recruited from homelessness or domestic violence services in the cities of Dublin, Cork and Galway. During this period, ethnographic observation was carried out at four service sites in Dublin city (which has recorded highest numbers of homeless persons in the country). Between November 2012 and September 2013 - approximately three years later - forty of these women were successfully tracked and re-interviewed Phase II of the research. Reliable information on the living situations of an additional nine women was attained at the time of follow-up, though it was not possible to re-interview these women. At Phase II of the study, ethnographic observation was again carried out in four service settings in Dublin city. The study’s retention rate is satisfactory given the recognised challenges associated with retaining transient populations in research of this kind. Methodologically, the study was guided by an interpretivist epistemology, which emphasises individuals’ personal understandings of their social worlds. The research therefore sought to give ‘voice’ to homeless women’s experiences and their perspectives on their lives and situations over time. Grounded in the rich qualitative data garnered insights also seek to expose how gender ideologies, norms and assumptions permeates policy and service delivery and these considerations not only impact on women’s trajectories through homelessness, but also bears influence on their sense of self and personal identity. The thesis concludes with a call for greater recognition of women’s homelessness in policy and service practice but also recommends that multiple responses are needed to prevent and resolve women’s homelessness, given the diversity of their experiences.
Keywords: Social Studies, Ph.D.; Ph.D. Trinity College Dublin